THE IMMUNOEXPRESSION PROFILE OF FGFR3 AND P53 IN PUNLMP AND UROTHELIAL BLADDER CARCINOMA AT HASAN SADIKIN GENERAL HOSPITAL - Suryanti, Sri; Agustina, Hasrayati; Mulyati, Sri (Indonesian Journal of Urology, 2020)
Objective: To obtain FGFR3 and p53 immunohistochemistry of PUNLM and UBC basic data profile. Material & Methods: This retrospective observational analytic study used a cross-sectional design on formalin-fixed paraffin-embedded (FFPE) from patients diagnosed as PUNLMP and UBC then performed FGFR3 and p53 immunohistochemical staining. Statistical analysis of immunoexpression data using SPSS 24.0. Results: There are three main immunohistochemistry pattern profiles of PUNLMP and UBC in this research data, i.e. FGFR3+ p53+, FGFR+ p53- and FGFR3- p53+. There were no Cis sample obtained. FGFR+ was showed in PUNLMP, LG-PUC, HG-PUC, IUBC (pT1, pT2, pT3, pT4) with decreased percentage sequentially. As many as 51 of 54(94.44%) IUBC samples showed combination pattern with p53+ while 3 other samples were p53-. Conclusion: The FGFR3 and p53 immunohistochemistry profile, separately or as a pattern of combination, is in accordance with the oncogenesis molecular pathway of UBC.